2015
DOI: 10.1016/j.vaccine.2014.11.038
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmodium berghei sexual stage antigen PSOP12 induces anti-malarial transmission blocking immunity both in vivo and in vitro

Abstract: Anti-malarial transmission-blocking vaccines (TBVs) aim to inhibit the transmission of Plasmodium from humans to mosquitoes by targeting the sexual/ookinete stages of the parasite. Successful use of such interventions will subsequently result in reduced cases of malarial infection within a human population, leading to local elimination. There are currently only five lead TBV candidates under examination. There is a consequent need to identify novel antigens to allow the formulation of new potent TBVs. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 43 publications
7
31
0
Order By: Relevance
“…This is surprising as this protein was independently identified in both the global comparative proteomics and the co-IP approaches. Moreover, similar to other OBC proteins identified in this study, the ortholog of this protein in the murine parasite P. berghei, PbPSOP12, has been detected on the gametocyte surface (39). Therefore, failure to detect PfPSOP12 in OBs could be an artifact of incorrect trafficking of the chimeric GFP-tagged fusion protein and further experiments using anti PfPSOP12 antibodies are needed to clarify this discrepancy.…”
Section: Discussionsupporting
confidence: 61%
“…This is surprising as this protein was independently identified in both the global comparative proteomics and the co-IP approaches. Moreover, similar to other OBC proteins identified in this study, the ortholog of this protein in the murine parasite P. berghei, PbPSOP12, has been detected on the gametocyte surface (39). Therefore, failure to detect PfPSOP12 in OBs could be an artifact of incorrect trafficking of the chimeric GFP-tagged fusion protein and further experiments using anti PfPSOP12 antibodies are needed to clarify this discrepancy.…”
Section: Discussionsupporting
confidence: 61%
“…However, there was a greater degree of reduction in oocyst prevalence in mosquitoes fed on mice immunized with the full-length protein (31.2%) as compared to that in mosquitoes fed on mice immunized with the partial rPSOP25 (25%) [26]. The TB activities of PSOP25 were comparable to those of PSOP12 [44], PSOP7 and PSOP26 [26] in the reduction of oocyst density and infection prevalence in DFA. Furthermore, monoclonal antibodies have been a valuable tool for the characterization of TBVs [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry data indicates it is expressed in gametocytes, ookinetes and oocyts in P. berghei and in P. falciparum (Florens et al, 2002; Hall et al, 2005; Ecker et al, 2008; Silvestrini et al, 2010). Live and immunofluorescence microscopy of PSOP12-GFPtagged parasites detected the protein on the surface of male and female gametocytes, gametes and ookinetes (Sala et al, 2015). Plasmodium berghei ΔPSOP12 parasites showed only a mild, non-significant reduction in oocyst production, resulting in normal numbers of sporozoites and normal transmission to mice (Ecker et al, 2008).…”
Section: 6-cys Proteins In the Sexual Stagesmentioning
confidence: 99%
“…Plasmodium berghei ΔPSOP12 parasites showed only a mild, non-significant reduction in oocyst production, resulting in normal numbers of sporozoites and normal transmission to mice (Ecker et al, 2008). Nevertheless, a recent vaccine study using baculovirus-expressed PbPSOP12 reported a small but significant transmission-blocking activity for antibodies to this protein both in vitro and in mice (Sala et al, 2015). Further characterization of SOP12 in P. falciparum and P. yoelii is required to determine whether robust blocking transmission activity can be achieved by targeting this protein.…”
Section: 6-cys Proteins In the Sexual Stagesmentioning
confidence: 99%